Genomic analysis of the lectotype specimens of European Ulva rigida and Ulva lacinulata (Ulvaceae, Chlorophyta) reveals the ongoing misapplication of names. Issue 2 (3rd April 2022) - Hughey, Jeffery R.; Gabrielson, Paul W.; Maggs, Christine A.; Mineur, Frédéric
ABSTRACT: Species of Ulva Linnaeus are nearly impossible to identify using morpho-anatomy due to their simple thallus structure and phenotypic plasticity. The current solution to this problem is to sequence DNA from field-collected specimens and match these sequences to those available in public DNA databases. However, because type specimens of many species have not been sequenced, the accuracy of these identifications is highly doubtful. Ulva rigida C.Agardh is reported to be one of the most widespread and ecologically important Ulva species, but these records are based on either morpho-anatomy or, more recently, on DNA sequences. High-throughput sequencing (HTS) was performed on the lectotype specimen of U. rigida from Cádiz, Spain to determine the correct application of the name. The analysis yielded its complete plastid genome. rbc L, tuf A and ITS sequences from the lectotype specimen differed at the species level from all U. rigida sequences deposited in public databases. Instead, the lectotype sequences of U. rigida were identical or very similar to sequences identified as U. rotundata Bliding (referred to by some as U. pseudorotundata Cormaci, G.Furnari & Alongi) from Ireland and Portugal, but not to the holotype of U. rotundata from Italy, which was identical to U. lactuca L. HTS of the lectotype of U. lacinulata (Kützing) Wittrock from Lesina, Croatia, a species morphologically similar to U. rigida with macroscopic marginal teeth, also yielded a complete plastid genome, with sequences identical or highly similar to GenBank U. armoricana Dion, Reviers & Coat, U . ' laetevirens ', U . ' rigida ' and U. scandinavica Bliding. Since U. lacinulata is the oldest validly published name, it is the correct one to apply to the globally distributed species that was previously but incorrectly known as U. rigida . Based on this genetic evidence, U. rigida is restricted to European waters and confirmed by DNA sequences from Ireland, Portugal and Spain. This analysis shows that many barcode species identifications and taxonomic conclusions in the genus Ulva are incorrect. Highlights: Ulva rigida was misapplied and is restricted to Atlantic Europe. Ulva lacinulata is the dentate species of Ulva distributed worldwide. Ulva rotundata is a heterotypic synonym of U. lactuca.